Effect of Acupuncture in Pain Management of Head and Neck Cancer Radiotherapy: Prospective Randomized Unicentric Study - Dymackova, Radana; Selingerova, Iveta; Kazda, Tomas; Slavik, Marek; Halamkova, Jana; Svajdova, Michaela; Slampa, Pavel; Slama, Ondrej (Journal of clinical medicine, 2021)
This prospective randomized open-label trial aimed to evaluate the role of acupuncture in the treatment of pain related to curative and adjuvant (chemo)radiotherapy of head and neck cancer. Patients in two arms (30 patients in each arm) underwent standard oncology therapy and standard supportive care with or without acupuncture. The stratification factors were the type of treatment and chemotherapy indication. The toxicity assessed was represented by pain rated on a 10-point pain scale and analgesic use. Average pain (AP) and the worst pain during the day (WP) were significantly lower in the acupuncture arm during radiotherapy (AP median 0.16 vs. 1.36, p < 0.001; WP median 0.90 vs. 1.96, p < 0.001) and three months after radiotherapy (AP median 0.07 vs. 0.50, p < 0.001; WP median 0.30 vs. 0.83, p = 0.002). The analgesic consumption between arms was statistically significantly different. A median of the proportion of days when the patients used analgesics was 8% and 32.5% during radiotherapy (p = 0.047) and 0% and 20.8% during three months after radiotherapy (p = 0.006) for the acupuncture and control arm, respectively. Results point out lower analgesic consumption and milder pain in acupuncture arm. Acupuncture consequently offers another alternative to standard treatment leading to a reduction in the toxicity of oncological treatment.
Keywords: head and neck cancer; acupuncture; pain; toxicity; radiotherapy